ANALISIS KEBUTUHAN (NEED ASSESMENT) DAN PERENCANAAN PROGRAM TAHFIDZ QUR’AN DENGAN MENGGUNAKAN METODE WAFA DI SDIT AL-MANAR PANGKALAN BUN - Sukinem Sukinem; Siminto Siminto (BADAN PENERBIT STIEPARI PRESS, 2023)
The purpose of this research is to analyze the needs (need assessment) and plan the tahfidz qur'an program using the wafa method at SDIT Al-Manar Pangkalan Bun. The research method used is qualitative. Data collection techniques are carried out by interviews, observation and documentation. Data collection techniques with interviews, observation and documentation. Data analysis techniques used 1) data reduction (data reduction), 2) data presentation (data displays and 3) conclusion drawing/verification. The results of this study are: needs analysis (need assessment) of the tahfidz qur'an program using the wafa method at SDIT Al-Manar Pangkalan Bun based on students' interest in extracurricular tahfidz Qur'an, it can be analyzed that the implementation of tahfidz Qur'an extracurricular activities at SDIT Al-Manar Pangkalan Bun is running smoothly. With quite a lot of enthusiasts, namely around 10 students in the first year. The tahfidz Qur'an extracurricular is a supporting field for SDIT Al-Manar Pangkalan Bun students to channel their talents and interests in the field of tahfidz Qur'an. Thus, the students of SDIT Al-Manar Pangkalan Bun can get closer to and love the Qur'an because of the tahfidz Qur'an extracurricular which becomes their intermediary to always love the Qur'an. Qur'an tahfidz extracurricular learning is also supported by using a special method that has been prepared by the ustadz/ustadzah, namely using the Wafa method. While planning the tahfidz qur'an program using the wafa method at SDIT Al-Manar Pangkalan Bun is carried out at the beginning of determining program objectives, followed by preparing a tahfidz program plan using the Wafa method. After that formulate what steps should be taken to implement the program. The tahfidz Al-Qur'an program is a program that is integrated with the school curriculum, the implementation of the program is carried out in the classroom. Planning the Wafa Qur'an learning process, especially in the Al-Qur'an Tahfiż program at SDIT Al-Manar Ajibarang has several stages, namely 5P, including the following: Opening, experience, teaching, assessment and closing. the application of the Wafa Method at SDIT Al-Manar has used the TANDUR strategy and in practice has also used the 5Ps well